The chronological position of the Lohne Soil in the Nussloch loess section: re-evaluation for a European loess-marker horizon - Kadereit, Annette; Kind, Claus-Joachim; Wagner, Günther A. (Quaternary science reviews, 2013)
The loess section of Nussloch in southwestern Germany is a key profile for the reconstruction of the terrestrial palaeo-environment of central Europe at the time of the Last Glacial and Interglacial. Recently, the significance of the site for palaeo-environmental and geoarchaeological research increased additionally, with the discovery of unique Palaeolithic cultural remains from anatomically and culturally modern humans that invaded southwestern Germany during the Weichselian (Würmian) Pleniglacial period. At Nussloch, a chrono-stratigraphical key position is taken by a Middle Pleniglacial Cambisol remain which, under the designation Lohne Soil, serves as an important pedostratigraphic marker horizon for the greater area. Repeatedly, Greenland interstadial (GIS) 8 was suggested as a likely period of soil formation for the Lohne Soil. This interpretation is yet not justified on the basis of published chronometric data. Critical assessment of the data points to a later period of soil formation, likely during GIS7 to GIS5. This conclusion is supported by a new set of radiocarbon ages for the Nussloch site which are presented here for the first time. Consequences of a revised chronology for correlations of Pleniglacial Cryosols below and above the Lohne Soil with Greenland interstadials are discussed. The implications are important for European loess research as the Nussloch section serves as a reference base for loess sections throughout Europe.
Gesehen am 13.04.2021
First published: 29 November 2012